Conversational Implicature in Selected Songs Lyrics by Brandi Carlile - Diana Rizki Putri (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2023)
Implicature is generally communicated through various media, such as song lyrics. The purpose of this research is to give comprehending to the readers and is expected to add their insight into implied meanings, especially the conversational implicature in song lyrics, so they can easily capture the true meaning that the lyricist poured into the song. The researcher analyzed conversational implicature using theory of implicature proposed by Yule (1996). The analysis in this research used qualitative research method by choosing the lyrics that contain conversational implicature. To support the analysis, the researcher used books, thesis, journals, and social media such as google and YouTube. The results of this research indicate that there are three types of conversational implicature, namely general conversational implicature, particularized conversational implicature, and scalar implicature. Then, the most dominant type of conversational implicature found in Brandi Carlile’s songs lyrics is particularized conversational implicature. Based on the result of analysis, conversational implicature is a common phenomenon in literary works, especially song lyrics.